Political leadership through the prism of a politician's psychological responsibility - YAREMCHYSHYN, Мarko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Leadership is a significant part of social existence. The political leader's personality is crucial for society's activity and development. Leaders' perception of the concept of responsibility promotes various forms of social development and the principles of societal existence. The political leader's personality is quite significant for the life activities of any socio-cultural environment. It is the personal characteristics of a socially significant political leader that provide answers to how they respond to certain circumstances that arise before them, as the nature of their decisions and perception of responsibility is reflected in society. The phenomenon of psychological responsibility is quite interesting in the context of a leader's personality, as this social role has a significant feature that manifests itself in the combination of the individual's personal-social skills, which are directed not only at their private, individual existence but also at the public, through the combination of interactions within society and their significance. The issue of psychological responsibility in the context of leadership is not sufficiently explored, but at the same time, it does not lose scientific relevance. The development of society encourages a deeper understanding of the individual characteristics of each personality, especially when they perform a socially important role, which involves reflecting the values of a particular social environment through their actions and image and meeting society's expectations. The concept of the psychological responsibility phenomenon is best reflected through the socio-cultural aspect and the essence of political leadership as an attribute of the socio-cultural environment and its peculiarities in the political sphere of different cultures.
Keywords: psychological responsibility; political psychology; leadership psychology; personality of a political leader